Intraoperative posture and workload assessment in vascular surgery. (April 2021) - Norasi, Hamid; Tetteh, Emmanuel; Money, Samuel R.; Davila, Victor J.; Meltzer, Andrew J.; Morrow, Melissa M.; Fortune, Emma; Mendes, Bernardo C.; Hallbeck, M. Susan
Abstract: Quantifying the workload and postural demand on vascular surgeons provides valuable information on the physical and cognitive factors that predispose vascular surgeons to musculoskeletal pain and disorders. The aim of this study was to quantify the postural demand, workload, and discomfort experienced by vascular surgeons and to identify procedural factors that influence surgical workload. Both objective (wearable posture sensors) and subjective (surveys) assessment tools were used to evaluate intraoperative workload during 47 vascular surgery procedures. Results demonstrate unfavorable neck and low back postures as well as high pain scores for those body segments. Additionally, workload from subjective surveys increased significantly as a function of operative duration, and mental workload was high across all procedure types. Neck postural risk exposure and physical demand were among the variables that increased with surgical duration, procedure type, and loupes used by the surgeons. Correlations among postural angles and pain scores showed consistency between the objective assessment and the subjective surveys for neck and trunk. The authors believe that the results of this study highlight the need for developing mitigating measures such as ergonomic interventions for vascular surgery. Highlights: High postural risk was associated with vascular surgery duration, open procedures, and adjunctive equipment such as loupes. The neck and trunk are the body segments at highest risk of pain/fatigue in vascular surgery. High scores for mental demand and complexity demonstrate high cognitive demand is associated with vascular surgery. Postural risk scores were positively correlated with subjective measurement of discomfort/pain in neck and trunk.